Developmental biology - Barresi, Michael J. F.; Gilbert, Scott F. (Oxford University Press, 2024)
The definitive market leader and decisive text for the field, Michael Barresi's Developmental Biology includes new features and active learning approaches to help students and instructors succeed, including electronic interviews, videos, tutorials, and case studies. Built on the excellent writing, accuracy, and enthusiasm of the original text, the new edition features on line resources that dynamically convey ideas and concepts, and creates an experience that meets the desires of those teaching Developmental Biology to a new generation"-- Provided by publisher.